[3-dimensional MR coronary angiography in the navigator technic for the primary diagnosis of coronary heart disease: a comparison with conventional coronary angiography] - Sandstede, J; Pabst, T; Kenn, W; Beer, M; Neubauer, S; Hahn, D (1999)
PURPOSE: Evaluation of three-dimensional MR coronary angiography with the navigator technique for the primary diagnosis of coronary artery disease (CAD) in patients with chest pain. MATERIALS AND METHODS: In this prospective study 20 patients with chest pain were examined with MR coronary angiography and conventional angiography. The three-dimensional MR coronary angiography was performed using a 1.5 T scanner with an ECG-triggered 3D-FLASH-sequence and retrospective respiratory gating in the navigator technique. The MR coronary angiography was evaluated by two radiologists blinded to the results of the conventional coronary angiography. RESULTS: One patient was excluded from further evaluation due to reduced image quality. Conventional coronary angiography excluded CAD in 8/19 patients, 11/19 patients overall showed 20 stenoses (> 50%) or occlusions. With MR coronary angiography, CAD was correctly excluded in 7 patients, one patient was false positive, one patient was false negative. 14/20 stenoses (> 50%) or occlusions were detected, 5 stenoses were diagnosed false positive. Sensitivity and specificity for primary diagnosis of CAD or detection of coronary artery stenoses were 91% and 88% or 70% and 91%, respectively. DISCUSSION: Using MR coronary angiography with the navigator technique in the primary evaluation of CAD, the diagnosis of stenoses or occlusions of the main coronary arteries is feasible.